Opening the Debate: How to Fulfill the Need for Physicians’ Training in Circadian-Related Topics in a Full Medical School Curriculum - Selfridge, Julia M (J Circadian Rhythms, 2015)
Background: Circadian rhythms are daily changes in our physiology and behavior that are manifested as patterns of brain wave activity, periodic hormone production, recurring cell regeneration, and other oscillatory biological activities. Their importance to human health is becoming apparent; they are deranged by shift work and jet-lag and in disparate conditions such as insomnia, sleep syndromes, coronary heart attacks, and depression, and are endogenous factors that contribute to cancer development and progression. Discussion: As evidence of the circadian connection to human health has grown, so has the number of Americans experiencing disruption of circadian rhythms due to the demands of an industrialized society. Today, there is a growing work force that experiences night shift work and time-zone shifts shaping the demands on physicians to best meet the needs of patients exposed to chronic circadian disruptions. The diverse range of illness associated with altered rhythms suggests that physicians in various fields will see its impact in their patients. However, medical education, with an already full curriculum, struggles to address this issue. Summary: Here, we emphasize the need for incorporating the topic of circadian rhythms in the medical curriculum and propose strategies to accomplish this goal.